Functionalization of Non-Activated C-H Bonds in the Synthesis of Vitamin D Metabolites and Analogs - Moman, Edelmiro (Current Topics in Medicinal Chemistry, 2014)
The development of non-microbial methods for the selective functionalization of non-activated C-H bonds has constituted a challenge, with important economical and environmental implications, for chemists for over a century. The present review provides a comprehensive and current compendium that illustrates the power of C-H functionalization and, namely, of remote functionalization strategies, to expeditiously access vitamin D analogs with intricate structures.
Keywords: Non-activated carbons